Modeling of Physiological Flows - Ambrosi, Davide; Quarteroni, Alfio; Rozza, Gianluigi; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2012)
This book offers a mathematical update of the state of the art of the research in the field of mathematical and numerical models of the circulatory system. It is structured into different chapters, written by outstanding experts in the field. Many fundamental issues are considered, such as: the mathematical representation of vascular geometries extracted from medical images, modelling blood rheology and the complex multilayer structure of the vascular tissue, and its possible pathologies, the mechanical and chemical interaction between blood and vascular walls, and the different scales coupling local and systemic dynamics. All of these topics introduce challenging mathematical and numerical problems, demanding for advanced analysis and efficient simulation techniques, and pay constant attention to applications of relevant clinical interest. This book is addressed to graduate students and researchers in the field of bioengineering, applied mathematics and medicine, wishing to engage themselves in the fascinating task of modeling the cardiovascular system or, more broadly, physiological flows.
Keywords: Mathematics; Human physiology; Biology -- Data processing; Differential equations, partial; Computer science -- Mathematics; Biomedical engineering; Mathematics; Computational Mathematics and Numerical Analysis; Human Physiology; Mathematical Modeling and Industrial Mathematics; Computer Appl. in Life Sciences; Partial Differential Equations; Biomedical Engineering